EFFECT OF LEACHING FRACTION DETERMINED BY TWO METHODS ON GROWTH AND YIELD OF MAIZE SUBMITTED TO SALT STRESS - Freitas, Emanuel Dias; de Lacerda, Claudivan Feitosa; Vieira, Juliana Matos; Bezerra, Bruno Gabriel Monteiro da Costa; Ribeiro, Aureliano De Albuquerque (IRRIGA, 2018)
EFFECT OF LEACHING FRACTION DETERMINED BY TWO METHODS ON GROWTH AND YIELD OF MAIZE SUBMITTED TO SALT STRESS1 EMANUEL DIAS FREITAS2; CLAUDIVAN FEITOSA DE LACERDA3; JULIANA MATOS VIEIRA4; BRUNO GABRIEL MONTEIRO DA COSTA BEZERRA5 E AURELIANO DE ALBUQUERQUE RIBEIRO6 1Parte da tese de doutorado do primeiro autor. Projeto financiado pelo CNPq; 2 Departamento de Engenharia Agrícola, Universidade Federal do Ceará – UFC, CEP: 60451-970, Fortaleza, CE, e-mail:emanueldiasfreitas@gmail.com; 3 Departamento de Engenharia Agrícola, Universidade Federal do Ceará – UFC, CEP: 60451-970, Fortaleza, CE, e-mail:cfeitosa@ufc.br; 4 Departamento de Ciência do Solo, Universidade Federal do Ceará – UFC, CEP: 60451-970, Fortaleza, CE, e-mail:julianamatosvieira@gmail.com; 5 Departamento de Engenharia Agrícola, Universidade Federal do Ceará – UFC, CEP: 60451-970, Fortaleza, CE, e-mail:brunog768@gmail.com; 6 Departamento de Engenharia Agrícola, Universidade Federal do Ceará – UFC, CEP: 60451-970, Fortaleza, CE, e-mail:alburibeiro@gmail.com. 1 ABSTRACT The aim of this study was to evaluate the effects of the leaching fraction determined by two methods in maize cultivated in a soil column and submitted to irrigation with water of different salinities. The experiment was conducted in the meteorological station of the Federal University of Ceará, Fortaleza - CE, in a completely randomized design, composed by four levels of irrigation salinity water (0.5, 2.0, 4.0 and 6.0 dSm-1) and two methods of determination of the leaching fraction. Each treatment had seven replicates. The plots were constituted by maize cultivated in soil columns, measuring 20 cm in diameter and 100 cm in length. The leaching fractions (LF) were defined as follows: A. Application of the LF calculated according to the formula proposed by Rhoades (1974), Rhoades and Merrill (1976); B. Application of the LF of 15% calculated from the soil water balance of the experimental plots. The results showed that plants that were irrigated with ECw of 0.5 and 4 dS m-1, the LF of 5 and15%, respectively, were able to minimize the effects of salinity. For ECw of 6 dS m-1, the LF of 15 and 92% showed no improvement in maize growth and yield. Keywords: Zea mays L. soil columns, saline water. FREITAS, E. D.; LACERDA, C. F. DE; VIEIRA, J. M.; BEZERRA, B. G. M. DA C. E RIBEIRO, A. DE A. EFEITO DA FRAÇÃO DE LIXIVIAÇÃO DETERMINADO POR DOIS MÉTODOS NO CRESCIMENTO E PRODUÇÃO DO MILHO SUBMETIDO A ESTRESSE SALINO 2 RESUMO Objetivou-se com o trabalho avaliar os efeitos da fração de lixiviação determinado por dois métodos na cultura do milho cultivado em coluna de solo e submetido a irrigação com água de diferentes salinidades. O experimento foi instalado na estação meteorológica da Universidade Federal do Ceará, Fortaleza – CE, em delineamento inteiramente casualizado, composto por quatro salinidade de água de irrigação (0,5, 2,0, 4,0 e 6,0 dS m-1) e duas formas de determinação da fração de lixiviação (FL). Utilizou-se sete repetições para cada tratamentos. As parcelas foram constituídas por milho cultivado em colunas de solo, medindo 20 cm de diâmetro e 100 cm de comprimento. As frações de lixiviação foram determinadas pelos seguintes métodos: A. Aplicação das FL de acordo com a fórmula de Rhoades (1974), Rhoades e Merrill (1976); B. Aplicação de FL de 15 % calculada a partir do balanço hídrico do solo. Os resultados mostraram que as plantas que foram irrigadas com CEa de 0,5, 4 dSm-1 as LF de 5 e 15%, respectivamente, foram capazes de dirimir os efeitos da salinidade. Para a CEa de 6 dSm-1 as LF de 15 e 92% não apresentaram melhoria no crescimento e produção do milho. Palavras-chave: Zea mays L., colunas de solo, água salina.